Space and Identity Construction: A Study of Female Singaporean Undergraduates in the UK - Wee, Alysia (Journal of International Students, 2019)
This article explores the significance of space in international student identity formation, focusing specifically on the experiences of female Singaporean undergraduate students in the UK. By examining three spatial scales (public, institutional, and room spaces), this article employs a mixed methods approach to investigate how identity is spatially situated and spatially performed. Findings indicate that public and institutional spaces shape students’ feelings of Otherness, racial hypervisibility, and individual invisibility. Students’ strategies for resisting negative identities also differ across these spaces. On the other hand, room spaces and their objects and layouts are agentically used by participants to perform their identities to others and themselves. Thus, this article highlights the importance of the spatial dimension in producing a nuanced understanding of international student identity formation.